Invasive alien plant species (IAPS) of Malagos Watershed in Calinan, Davao City and Mt. Musuan, Bukidnon - Abas, Cindy Grace S. (Sylvatrop, 2016)
This study compared the species richness and diversity of Invasive Alien Plant Species (IAPS) between Malagos Watershed, Calinan, Davao City, a landscape watershed near an urban area and Mt. Musuan, Bukidnon, a lower montane ecological research site. Whittaker plots were used in sampling. Identified IAPS in Malagos Watershed, were Sphaerostephanos sp., Elephantopus scaber Linn., Colocasia esculenta (L.) Nakai, and Asystasia gangetica CV. Present in both sites were Piper aduncum L., Gmelina arborea Roxb, Spathodea campanulata Beauv., and Chromolaena odorata (L.) King. Also encountered in the Mt. Musuan plots were Acacia mangium Willd., Flagellaria indica L., Lantana camara L., Leucaena leucocephala, Lygodium japonicum, Mikania micrantha, Salvinia molesta, and Swietenia macrophylla. The IAPS in Malagos Watershed obtained index of H = 0.946. Mt Musuan obtained D-1 = 0.80317; evenness of 0.74727; H = 2.48491.